Importance of culture in measuring tribal crime seriousness: scoping review of crime seriousness indices - Riley, Lorinda (Journal of ethnicity in criminal justice, 2024)
Understanding crime trends provides policymakers with needed information to effectively use scarce resources to keep communities safe. Native nations in the US, who retain criminal and civil jurisdiction on their lands, rely on national data collected by the federal government with little tribal input. These data may not accurately reflect the community’s situation or the values they hold. Developing a tribal crime seriousness index may provide an elegant way to bridge this gap. This paper catalogs and identifies the methods for developing crime seriousness indices and provides a critical discussion of the role culture plays in the conceptualization of crime.